THE ESTABLISHMENT OF SECULAR PEDAGOGICAL EDUCATION AT LVIV UNIVERSITY OVER THE LAST THREE DECADES OF THE ХІХ CENTURY - Теодор Лещак (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article contains overview of reasons and prerequisites of incipience of secular pedagogical training of Lviv University students in the context of European educational processes. The variety of theoretical and practical courses of the Philosophy Department in the end of XIX century is analyzed. The study showed that the formation of a secular pedagogical training at Lviv University in the last third of the XIX century was the logical consequence of a number of educational reforms in Austria after the abolition of the Concordat in 1870. In the context of these reforms was demarcated teacher training students in the theological and philosophical faculties, in particular, have been developed and introduced separate nomenclature training courses based on individual organizational, financial and staffing.